Evaluating a Collaborative Approach to Improve Prior Authorization Efficiency in the Treatment of Hepatitis C Virus. Issue 3 (July 2017) - Dunn, Emily E.; Vranek, Kathryn; Hynicka, Lauren M.; Gripshover, Janet; Potosky, Darryn; Mattingly, T. Joseph
Abstract : Objective: A team-based approach to obtaining prior authorization approval was implemented utilizing a specialty pharmacy, a clinic-based pharmacy technician specialist, and a registered nurse to work with providers to obtain approval for medications for hepatitis C virus (HCV) infection. The objective of this study was to evaluate the time to approval for prescribed treatment of HCV infection. Methods: A retrospective observational study was conducted including patients treated for HCV infection by clinic providers who received at least 1 oral direct-acting antiviral HCV medication. Patients were divided into 2 groups, based on whether they were treated before or after the implementation of the team-based approach. Student t tests were used to compare average wait times before and after the intervention. Results: The sample included 180 patients, 68 treated before the intervention and 112 patients who initiated therapy after. All patients sampled required prior authorization approval by a third-party payer to begin therapy. There was a statistically significant reduction ( P = .02) in average wait time in the postintervention group (15.6 ± 12.1 days) once adjusted using dates of approval. Conclusions: Pharmacy collaboration may provide increases in efficiency in provider prior authorization practices and reduced wait time for patients to begin treatment.